KAJIAN PENGGUNAAN LAHAN HUTAN DAN PERUBAHANNYA MENGGUNAKAN DATA CITRA SPOT LANDSAT DAN RADAR - Endom, Wesman; Haryono, Haryono (Pusat Penelitian dan Pengembangan Hasil Hutan, 2004)
To enhance effectiveness of natural resources evaluation an assessment on the trend of land- use and its impacts is necessary. This is needed by regions which are interacted each others and covering large areas. A remote sensing technology is a reliable and appropriate choice for such area. A study on the land-use assessment was employed using manual method through the implementation of Spot, Landsats, and Radar imageries. The results were as follows:1) Until the year 1980, the concession area situated at Long Nah, administratively under authority of PT Inhutani I. East Kalimantan were mostly still covered by virgin forest with occasional and scattered small villages2)Â Manual interpretation using imageries of Spot, Landsats and Radars disclosed the following results: (a) Spot imageries turned out to be 64. 7% as the correct figure and 35.3% as the false figure;, (b) Landsat imageries interpreted 53.3% as correct and 46.7%Â as false; (c) Radar imageris conducted in March and April 1998 revealed 38. 1% as correct and 61.9% as false.3) Changes forest land-use during the period 1980-1998 occurred in low-land dry forest andpartly in swampy forest, which were further converted to the plantation forest. Meanwhile, the changes for other land-uses among others agriculture were almost insignificant ( less than 3%). This is because soil layers in the corresponding land were thin and acidic rendering unsuitable for agriculture activities.4)Â In order to reduce high commission error, the appropriate number of strata relevant to the land-use interpretation should not be too detailed but adequately established as simply aspossible.